Affective Evaluation Model for Islamic Religious Education: Development and Application in Madrasah Aliyah and Pondok Pesantren - Tsani, Iskandar (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objective of this research is to develop an evaluation model for the affective aspect of Islamic Religious Education (IRE) in Madrasah Aliyah and Pondok Pesantren. This is a developmental research project that employs a mixed-methods approach (quantitative and qualitative), comprising three phases: pre-development, development, and dissemination. The model comprises two components: a guide for the evaluation model and the evaluation instruments, which consist of questionnaires, observation sheets and self-evaluation questionnaires. The validity of the evaluation instruments was determined through the application of expert judgement, while reliability was assessed using Cronbach’s alpha. The construct validity of the instruments, including the questionnaires and observation sheets, was determined through the application of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The findings revealed that the IRE affective evaluation model (AEIRE) is constituted of three principal components. The instruments demonstrated a satisfactory fit with the Input, Process, and Output components. The model was deemed to be effective for use in Madrasah Aliyah and Pondok Pesantren, and the guide for its application was well received by IRE teachers.